Aerodynamics - Gorji-Bandpy, Mofid; Aly, Aly-Mousaad (IntechOpen, 2021)
Aerodynamics, the study of air motion around solid objects, allows us to understand and measure the dominating forces acting on aircrafts, buildings, bridges, automobiles, and other structures. The forces that result in an aircraft overcoming gravity and drag are called thrust and lift. Various parameters such as geometrical configurations of objects, as well as physical properties of air, which may be functions of position and time, affect those forces. This book covers some of the latest studies regarding the application of the principles of aerodynamics to the design of many different engineered objects. This book will be of interest to mechanical and aerospace engineering students, academics, and researchers who are looking for new insights into this fascinating branch of fluid mechanics.